Environmental Effects and Management Strategies of the Herbicides - Basu, Sayantani; Rao, Y. Vasudeva (International Journal of Bio-resource and Stress Management, 2020)
India has wide range of agro-climates and soil types and highly diverse agriculture farming systems with different types of weed problems. So, herbicides are the integrated part of the general cropping systems. In general, herbicides are formulated in such a way that they degrade from the environment after completion of their intended work, but a few of them persist in the environment and cause a serious hazard to the succeeding crop and also to the surrounding environments. Hence, a proper knowledge of herbicides is important to understand the management procedure, organization and hierarchy of the herbicides. It also provides an imminent idea to herbicide resistance, which continues to be a problem in sustainable agricultural management. In this review, the herbicides used in India, negative impact of herbicides on the environment, persistency of herbicides, their dissipation methods and different management practices to avoid/minimize herbicide carry-over effects were discussed. The combine effects of bioaugmentation and biostimulation along with organic matter addition might be a promising technology to accelerate the biodegradation. Apart from these, extensive field evaluation studies with other tools like crop rotation and increment of the organic matter content is definitely a promising technique for managing the herbicide persistence. Bioherbicides, a biological control agent for weeds, and transgenic approaches can be a good alternative for chemical herbicides in future. They provide high degree of specificity of target weed and have no effect on non-target, beneficial plants or man and do not form any residues in the environment.